Effect of Recent Spinal Cord Injury on Wnt Signaling Antagonists (Sclerostin and Dkk‐1) and Their Relationship With Bone Loss. A 12‐Month Prospective Study. (June 2015) - Gifre, Laia; Vidal, Joan; Carrasco, Josep L; Filella, Xavier; Ruiz‐Gaspà, Silvia; Muxi, Africa; Portell, Enric; Monegal, Ana; Guañabens, Nuria; Peris, Pilar
Abstract Spinal cord injury (SCI) has been associated with a marked increase in bone loss and bone remodeling, especially short‐term after injury. The absence of mechanical load, mediated by osteocyte mechanosensory function, seems to be a causative factor related to bone loss in this condition. However, the pathogenesis and clinical management of this process remain unclear. Therefore, the aim of the study was to analyze the effect of recent SCI on the Wnt pathway antagonists, sclerostin and Dickkopf (Dkk‐1), and their relationship with bone turnover and bone mineral density (BMD) evolution. Forty‐two patients (aged 35 ± 14yrs) with a recent (<6months) complete SCI were prospectively included. Sclerostin and Dkk‐1, bone turnover markers (bone formation: PINP, bone ALP; resorption: sCTx) and BMD (lumbar spine, proximal femur, total body and lower extremities [DXA]) were assessed at baseline and at 6 and 12 months. The results were compared with a healthy control group. 22/42 patients completed the 12‐month follow‐up. At baseline, SCI patients showed a marked increase in bone markers (PINP and sCTx), remaining significantly increased at up to 6 months of follow‐up. Additionally, they presented significantly increased Dkk‐1 values throughout the study, whereas sclerostin values did not significantly change. BMD markedly decreased at the proximal femur (‐20.2 ± 5.4%, p < 0.01), total body (‐5.7 ± 2.2%, p = 0.02) and lower extremities (‐13.1 ± 4.5%, p = 0.01) at 12 months. Consequently, 59% of patients developed densitometric osteoporosis at 12 months. Patients with higher Dkk‐1 values (>58 pmol/L) at baseline showed higher sublesional BMD loss. In conclusion, this study shows that short‐term after SCI there is a marked increase in bone turnover and bone loss, the latter associated with an increase in Dkk‐1 serum levels. The persistence of increased levels of this Wnt antagonist throughout the study and their relationship with the magnitude of bone loss suggests a contributory role of this mediator in this process. © 2014 American Society for Bone and Mineral Research.